Modernisasi Manajemen Kelas Pendekatan Otoriter Mengatasi Permasalahan Pembelajaran - Satrio Ikhsan Nurhakim; Adrias Adrias; Aissy Zulkarnaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Educational management that is too soft has changed the characteristics of students and made them no longer responsible and negligent of their obligations. Thus, a more assertive and authoritarian class management is needed to train students' abilities to obey the rules and understand their obligations. By studying case studies that have been conducted by previous researchers, researchers will make a summary and discussion to integrate various previous studies. After summarizing from various sources of literature, the results obtained were that authoritarian class management had more negative impacts than positive impacts, but the positive impacts produced were very useful for students' lives in the future, while the positive impacts had more influence on the pleasure and interest factors of students who did not enjoy the class management system implemented by their teachers. However, it can be concluded that authoritarian class management does not necessarily have to be rejected but should be implemented but integrated with other methods so that learning can be accepted by students.